Integrated Gas Diffusion Electrode with High Conductivity Obtained by Skin Electroplating for High Specific Power Density Fuel Cell. Issue 2 (22nd December 2022) - Ning, Fandi; Chai, Zhi; Dan, Xiong; Liu, Pei; Wen, Qinglin; Pan, Saifei; He, Can; Li, Yali; Jin, Hanqing; Li, Wei; Xu, Pengpeng; Chen, Jiafan; et al.
Abstract: Smaller volume/weight and higher output power/energy density are always the goals of electrochemistry energy devices. Here, a simple strategy is proposed to prepare an integrated gas diffusion electrode (GDE) with high conductivity through skin electroplating. The skin electroplating is the combination of magnetron sputtering and spatial confinement electroplating. The electroplated metal obtained by skin electroplating is uniformly, continuously, and tightly attached to the surface of carbon paper like a layer of skin. Uniform and continuous electroplating metal layer endows the integrated electrode excellent conductivity with the square resistance as low as 27 mΩ sq −1 . In application, the self‐breathing fuel cell with 1 cm 2 active area can harvest ultrahigh volume specific power density (20.9 kW L −1 ). Additionally, the weight of the fuel cell stack (23 W) with the integrated electrode is only 20 g, which is only 7% of the commercial stack with the same power. The mass specific power density reaches 1150 W kg −1, which is 15 times of the commercial stack. Outstandingly, the stack can charge 4 mobile phones at the same time. More importantly, the skin electroplating provides an effective strategy to improve the specific power density of other energy devices including Zn‐air batteries, Li‐air batteries, and so on. Abstract : Light weight self‐breathing proton exchange fuel cell with high specific power density is prepared by a high conductivity integrated electrode. The mass and the volume of the fuel cell are 37.5 mg and 0.017 cm 3 . The fuel cell can be placed on the dandelion. The volume specific power density of the fuel cell is 20.9 kW L −1 .